Classification of Superbaplogroup M in Chinese Population of Peninsular Malaysia - Mokhtaruddin, Nor Alfarizan (Universiti Sains Malaysia, 2006)
The evolution of the human mitochondrial genome is characterized by the emergence of ethnically distinct lineages or haplogroups. Mitochondrial DNA (mtDNA) haplogroups were identified on the basis of the presence or absence of a restriction enzyme polymorphism in the coding region along with the sequence polymorphisms in the control region. This study was undertaken to analyze the mtDNA polymorphism in random population of Chinese ethnic of Peninsular Malaysia. A total number of 44 buccal cells samples were collected and subjected to extraction, followed by amplification by PCR and digestion process through restriction fragment length polymorphism (RFLP) analysis. Alu I restriction enzyme was used to detect polymorphism at nucleotide position 10397 in the mtDNA coding regions. Result shows that out of 44 samples, 21 of them were identified to be having an Alu I site gain at nucleotide position 10397, which classified them under the superhaplogroup M.